Analisis Framing Pemberitaan Kasus Obstruction of Justice Ferdy Sambo dalam Media Online Asing - Al Fatah, Muhammad Ghozy; Irfanuddin, Fahmi (Wardah, 2023)
Abstract. This research aims to reveal or understand the frame built by foreign media regarding the reporting of the Obstruction of Justice case involving Inspector General Ferdy Sambo and how these frames were built, using Robert N. Entman’s analysis technique. Media as the fourth estate have a big influence in building the public perception of an event. The increasing development of information technology certainly increases the possibility of forming public opinion through digital-based media which possess a greater level of flexibility and accessibility than conventional media. The Obstruction of Justice case is important to research considering the popularity of this case for several months and how this case is an illustration of the upholding of justice in Indonesia. The research used a descriptive qualitative approach and referred to the framing analysis technique formulated by Robert Entman by focusing on four analysis aspects to reveal the frames constructed by media. The research revealed that the frame built by foreign online media was in the form of a narrative of the National Police as an institution with problems internally and externally, and the Obstruction of Justice case as well as a series of problems that followed were the result of problems within the National Police. In this case, foreign online media emphasized the issue of a culture of impunity as the cause of obstruction of law enforcement in Indonesia which seemed sharp upwards but blunt downwards. Keywords: Framing Analysis, Obstruction of Justice, Ferdy Sambo, Foreign Online Media